The Effect of Incubation Time on the Quality of Post-Thawed Ram Sexed Sperm - Nurcholidah Solihati; Siti Darodjah Rasad; Rangga Setiawan (Universitas Sebelas Maret, 2024)
Objective: The sperm sexing using an albumin column requires an incubation process at a certain temperature for sperm to move through the albumin layer. It is thought that the incubation time can influence the quality of the semen resulting from post-thawing sexing. The aim of this research was to determine the effect of incubation time on the quality of sexed sperm post-thawing and to find out the optimum incubation time that provide the best sperm quality.Methods: This research was carried out in a completely randomized design, using three incubation times (T1= 45 minutes, T2= 60 minutes, T3= 75 minutes) with six replications. The parameters consisted of motility, abnormality and acrosome integrity of sexed sperm in the upper and bottom fractions. Data were analyzed using analysis of variance (Anova) and continued with the Duncan test.Results: The results showed that the incubation time had a significant effect on motility, intact acrosome cap and recovery rate, but had no significant effect on abnormality of post thawed sexed sperm. For both the upper and bottom fraction, incubation times of 45 and 60 minutes produced the best motility and recovery rate compared to 75 minutes, but the best intact acrosome cup was obtained from an incubation time of 45 minutes.Conclusions: Based on the research results, it can be concluded that the length of incubation time influences the quality of post thawed ram sexed sperm, and 45 minutes is the optimal incubation time to provide the best quality.